Implementation of Digital Literacy in Increasing the Learning Independence of Fourth-Grade Students at SDN 1 Krandon - Faadhilah Estining Tyas; Sukartono (South Sulawesi Education Development (SSED), 2024)
Indonesia is currently entering the 21st century, where almost all activities are side by side with technology, one of which is information that can be published on digital media and can be seen anywhere and at any time. The existence of digitalization, which is widespread throughout the world, gives rise to two opposing sides, namely challenges and opportunities. The use of digital technology can be a good opportunity in the world of education, namely by implementing digital-based literacy as an effort by educators to familiarize themselves with a culture of literacy and familiarize students with using digital technology wisely. With the implementation of digital literacy in schools, students are free to search for information from various sources independently. The aim of this research is to describe the implementation of digital literacy in increasing the learning independence of fourth-grade students at SD N 1 Kradon, describe the supporting and inhibiting factors in the use of digital literacy in increasing the learning independence of fourth-grade students at SD N 1 Kradon, and describe solutions to overcome factors inhibiting the use of literacy. digital in increasing the learning independence of fourth-grade students at SD N 1 Kradon. This research is descriptive qualitative research, which is a research process to understand a phenomenon by creating a comprehensive general picture presented in the form of words. Therefore, the data collected in qualitative research is presented in the form of descriptive text or narrative data. Data collection was carried out through interviews, observation, and documentation. Validity of data using source triangulation and techniques. The data analysis techniques used in this research are data collection, data reduction, data presentation, and drawing conclusions. The results of this research show that the implementation of digital literacy in schools can increase student learning independence. Implementation of digital literacy can increase students' learning motivation, responsibility, initiative, and self-confidence.